Relationship between the Learning Environment and the Learning Activities of Students During the Covid-19 Pandemic at MDTA Nurul Ilmi, Ulakan Tapakis District, Padang Pariaman Regency - Ulfa Trisna Wulandari; Tasril Bartin (Universitas Negeri Padang, 2021)
This research was motivated by the low learning activity of students at Madrasah Diniyah Takmiliyah Awaliyah Nurul 'Ilmi which allegedly had something to do with the students' learning environment. The purpose of this study is to reveal a description of the learning environment of students, the learning activities of students at MDTA Nurul 'Ilmi, and to reveal the relationship between the learning environment and the learning activities of students. This type of research is a descriptive correlational study with a quantitative approach. The population of this study was students from class I to class IV MDTA Nurul Ilmi in 2020, amounting to 59 people and a sample of 60%, namely 35 people with a sampling technique, namely stratified random sampling. The data collection technique used was a questionnaire and the tools used were questionnaires. The data analysis technique uses the percentage formula and the product-moment formula. The results of this study indicate that: 1) the learning environment of students at MDTA Nurul 'Ilmi is low; 2) the learning activities of students at MDTA Nurul 'Ilmi are classified as low; 3) there is a significant relationship between the learning environment and the learning activities of students during the Covid-19 Pandemic at MDTA Nurul 'Ilmi, Ulakan Tapakis District, Padang Pariaman Regency. The suggestion of this research is that it is hoped that the teacher creates a comfortable learning atmosphere in the classroom for students so that the learning activities of students increase.Keywords: Learning Environment, Learning Activity